Impacts of Alexandria Catechetical School’s Sacred-Secular Education and its Implications for Theological Institutions in Nigeria - Anzaku, Danjuma Umaru (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This article explores how the Alexandria Catechetical School educational system which combined sacred and secular learning can be applied in theological institutions in Nigeria. The study adopts a qualitative research approach, utilizing historical analysis and literature review to explore the historical context and educational practices of the Alexandria Catechetical School. Major findings from the study reveal that such holistic approach to education did not only enrich the theological understanding of students but also equipped them with practical and contextualized skills for engaging with the secular world. The study also highlights how theological institutions in Nigeria can apply similar system such as interdisciplinary training, contextualization and community engagement, spiritual and moral values, discipleship through godly leadership by example and development of entrepreneurship skills in order to produce all-round competent manpower to address current challenges confronting the Nigerian church and society. The study recommends that theological institutions in Nigeria should consider incorporating elements of the Alexandria Catechetical School's educational system to better prepare students for the challenges of the modern world. These include integrating more secular subjects into the curriculum, providing practical training opportunities, and fostering a culture of intellectual curiosity and critical thinking. With holistic approach to education, theological institutions in Nigeria will not only be better in equipping their students to engage with the complexities of the contemporary world, but will also attract public relevance while remaining rooted in their sacred missions.